Pengaruh Pengalaman PKL sebagai Sarana Pembentukan Kepercayaan Diri dan Kesiapan Kerja Siswa SMK - Rian Mahesa; Adel Lia Mardiana; Rijal Abdullah; Indah Sartika; Hendra Hidayat (Program Studi Pendidikan Teknik Mesin Fakultas Keguruan dan Ilmu Pendidikan Universitas Sriwiajaya, 2025)
This study aims to analyze the influence of Field Work Practice (PKL) experience on the formation of self-confidence and work readiness of vocational high school students through a quantitative approach with a survey method using a Likert scale instrument, and the results of statistical analysis show that PKL has a significant influence, especially through aspects of knowledge and skills acquired during industrial practice, while the self-confidence of grade XII students who have carried out industrial work practice (PKL) does not provide a significant contribution, so this study confirms that the effectiveness of PKL as a character builder and work readiness is highly dependent on the quality of the industrial environment, consistent guidance, and the suitability of the program to the needs of the ever-evolving world of work.